Histologic Features of Prepubertal and Pubertal Reproductive Development in Female Sprague-Dawley Rats. (February 2014) - Picut, Catherine A.; Remick, Amera K.; Asakawa, Midori G.; Simons, Michelle L.; Parker, George A.
In response to growing concerns that environmental chemicals may have adverse effects on human health by altering the endocrine system, the Endocrine Disruptor Screening Program (EDSP), under the auspices of the United States Environmental Protection Agency (U.S. EPA), recently instituted a Tier I battery of tests including a female pubertal assay. This assay requires dosing of female rats from postnatal day (PND) 22 through PND 42 (or 43), the period of pubertal development in the rat, to identify test articles that may have estrogenic or antiestrogenic effects, or may alter hormones or neurotransmitters. While certain landmarks in female rat reproductive development are published, little is published on the microscopic appearance of the female reproductive tract during prepubertal and pubertal development. In this study, reproductive tissues from three female Sprague-Dawley rats were collected each day from PND 20 through PND 50, such that tissues from a total of 93 rats were collected throughout the prepubertal and pubertal period. Tissues were formalin-fixed, trimmed, paraffin-embedded, sectioned at 5-µm thickness, and examined microscopically. The major histologic features of the female reproductive tract throughout this critical period were described in detail. This information will help pathologists interpret findings observed in female pubertal assays.